Hubungan Status Gizi dengan Kejadian Anemia pada Remaja Putri di SMK Swadaya Wilayah Kerja Puskesmas Karangdoro Kota Semarang Tahun 2013 - Wina Mariana; Nur Khafidhoh (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2013)
Anemia is a major nutritious problem in Indonesia, which is caused by iron deficiency. Among its impacts are brain power reduction (power of thought), concentration, and health problems. This general purpose is to know the connection between dietary rules and nutritional status with phenomenon of anemia which was suffered by the adults at SMK Swadaya, Semarang in 2013. This research used design which was applied is correlation study with crossectional approach. The research took place at SMK Swadaya, Semarang in 2013. The result showed The samples in the research are 84 respondents with questionnaires and Hb digital as the research instruments. Analyses of the data are unuvariat with frequency table and bivariat with continuity correction test. The results for the most part respondent with dietery rules are irreguler 61,1%, respondents with bad nutrition status 57,1%, dan respondents with anemia 71,4%. In data processing we examined the normality through Kolmogorov-Smirnov test with the result ρ 0,05 so that data distribution was abnormal. Examination with continuity correction between nutritional status with the phenomenon of anemia got ρ value= 0,089 (0,05), so there is not connection between nutritional status with phenomenon of anemia to young women at SMK Swadaya Semarang in 2013.